Effectiveness of botulinum toxin injection in the treatment of de novo OAB symptoms following midurethral sling surgery. Issue 3 (March 2016) - Miotla, Pawel; Futyma, Konrad; Cartwright, Rufus; Bogusiewicz, Michal; Skorupska, Katarzyna; Markut-Miotla, Ewa; Rechberger, Tomasz
Abstract Introduction and hypothesis Intravesical onabotulinumtoxinA (Botox®) is effective for idiopathic overactive bladder (OAB) symptoms. Our primary objective was to compare the efficacy of onabotulinumtoxinA for women with de novo OAB after midurethral sling (MUS) surgery and women with idiopathic OAB. Methods Women enrolled in this prospective study had idiopathic (n = 53) or de novo (n = 49) OAB symptoms after MUS, with at least one episode of urgency urine incontinence per day. OnabotulinumtoxinA (100 U) was administered in 20 intradetrusor injections. Postvoid residual volumes were checked at 2, 4 and 12 weeks. Participants completed a 3-day bladder diary and the King's Health Questionnaire (KHQ) before and 12 weeks after treatment. Results After 12 weeks, 22 patients (41.5 %) in the idiopathic OAB and 19 patients (38.8 %) in the de novo OAB groups were completely dry. OnabotulinumtoxinA injections had a significant benefit within both groups (p <0.001) to decrease both the daily numbers of voids (−2.39 and −2.0) and incontinence episodes (−1.38 and −1.44), with no significant difference between groups. We observed an increase of mean voided volume of >90 ml in both groups. Urinary retention was observed in four patients. Conclusions We observed similar improvement in OAB symptoms after intravesical onabotulinumtoxinA injections within both groups. The rates of retention and requirement for catheterization even for women with a prior MUS were acceptable. These observational data provide evidence that onabotulinumtoxinA can effectively treat patients with OAB following stress urinary incontinence surgery.